The European Cancer Patient’s Bill of Rights, update and implementation 2016 - Lawler, Mark; Zur Hausen, Harald; Chevalier, Thierry Le; Johnston, Patrick; Selby, Peter (ESMO open, 2016)
In this implementation phase of the European Cancer Patient’s Bill of Rights (BoR), we confirm the following three patient-centred principles that underpin this initiative: - The right of every European citizen to receive the most accurate information and to be proactively involved in his/her care.The right of every European citizen to optimal and timely access to a diagnosis and to appropriate specialised care, underpinned by research and innovation.The right of every European citizen to receive care in health systems that ensure the best possible cancer prevention, the earliest possible diagnosis of their cancer, improved outcomes, patient rehabilitation, best quality of life and affordable health care. - - The key aspects of working towards implementing the BoR are: - Agree our high-level goal. The vision of 70% long-term survival for patients with cancer in 2035, promoting cancer prevention and cancer control and the associated progress in ensuring good patient experience and quality of life.Establish the major mechanisms to underpin its delivery. (1) The systematic and rigorous sharing of best practice between and across European cancer healthcare systems and (2) the active promotion of Research and Innovation focused on improving outcomes; (3) Improving access to new and established cancer care by sharing best practice in the development, approval, procurement and reimbursement of cancer diagnostic tests and treatments.Work with other organisations to bring into being a Europe based centre that will (1) systematically identify, evaluate and validate and disseminate best practice in cancer management for the different countries and regions and (2) promote Research and Innovation and its translation to maximise its impact to improve outcomes.
Online issue publication January 06, 2017
Gesehen am 20.05.2020